Impact of pesticide tolerant soil bacteria on disease control, plant growth promotion and systemic resistance in cowpea - Bandopadhyay, Anuradha; Roy, Tina; Das, Nirmalendu (Journal of Environmental Engineering and Landscape Management, 2021)
Cowpea, an annual legume, suffers from several disease symptoms caused by Macrophomina phaseolina. Rhizobacteria isolated from pesticide infested soil, identified by blast analysis as Bacillus cereus, Bacillus safensis, Pseudomonas donghuensis and Pseudomonas aeruginosa ascertained tolerant to at least 0.1% pesticides viz. methomyl, imidacloprid and carbendazim. In vitro antagonism against pathogen exhibited maximum by P. aeruginosa 63%. All rhizobacteria were bestowed with attributes responsible for pathogen control and plant growth promotion. Field evaluation resulted highest 75% disease control, enhancement of length, nodule counts, biomass or yield per plant by P. aeruginosa. All rhizobacteria induced systemic resistance in cowpea under challenged inoculation with pathogen by augmenting defensive enzyme production. Highest Phenylalanine Ammonia Lyase activity was expressed in P. aeruginosa treated plants 1.02 μMoles/ml/min, Polyphenol Oxidase by P. donghuensis 1.39 μMoles/ml/min, Chitinase by B. cereus 0.745 μMoles/ml/min and 400 percent relative activity of Peroxidase by P. aeruginosa. The rhizobacteria were prospective for plant disease control, growth promotion and as immunity boosters in pesticide and heavy metal infested toxic environment.